BEBERAPA FAKTOR YANG MEMPENGARUHI PENDAPATAN KELUARGA PADA UMKM DI KECAMATAN KUTA UTARA - Sari, Meita Puspita; Karmini, Ni Luh (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.10.TAHUN 2019, 2019)
Micro, Small and Medium Enterprises (MSMEs) are businesses that easily live in the midst of society and play an important role in the economic of society and also the country. The objectives to be achieved in this study are: 1) analyzing the effect simultanly of the number of dependents, age, time allocation and experience on family income in MSME in sub-district Kuta Utara 2) analyzing the effect partially of the number of dependents, age, time allocation and experience on family income in MSMEs in sub-district Kuta Utara, 3) to analyze the role of experience in moderating the effect of time allocation on family income of UMKM in sub-district . The data analysis technique used was moderating regression analysis, with a total sample of 62 samples. The results of this study are the 1) number of dependents, age, time allocation and experience simultanly influence family income in MSMEs in sub-district Kuta Utara 2) number of dependents, age, time allocation and experience positively influencing family income in MSMEs in sub-district Kuta Utara, 3) experience weakens influence of time allocation on family income in MSMEs in sub-district Kuta Utara.